2022
DOI: 10.1021/acsomega.2c03799
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Control of CaO–Al2O3–SiO2 Glass Ceramics by Oxidation and Mixing with Nucleation Agents

Abstract: Microstructural control of CaO–Al 2 O 3 –SiO 2 (CAS) glass ceramics (GCs) was achieved by oxidation and mixing with nucleation agents. CAS GCs were precipitated with hexagonal platy particles of metastable CaAl 2 Si 2 O 8 layered crystals (CAS GC-H), which are typically prepared under a reductive atmosphere that forms metallic Mo or W particles as nucleation agents. The aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(44 citation statements)
references
References 34 publications
7
37
0
Order By: Relevance
“…1, left), in good agreement with our previous studies. 19–21,24,27,31 By contrast, Cullet-Eu 2+ was yellowish (Fig. 1, right), consistent with the results of the previous studies in which Eu 2+ -doped glass specimens were reported to be yellow.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…1, left), in good agreement with our previous studies. 19–21,24,27,31 By contrast, Cullet-Eu 2+ was yellowish (Fig. 1, right), consistent with the results of the previous studies in which Eu 2+ -doped glass specimens were reported to be yellow.…”
Section: Resultssupporting
confidence: 91%
“…28 However, such coloration was not observed in the colorless CAS glass prepared by the oxidative melting of glass cullet containing metallic W particles in our previous study. 19,21 Therefore, the oxidation of metallic W particles in the CAS glass with the present composition likely dose not generate a glass specimen with W cluster coloration. Meanwhile, the colorless glass that never showed bulk crystallization was obtained when the raw material of CAS glass was melted without addition of carbon.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations